2005
DOI: 10.1021/bi050943e
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acid Transport in Sister of P-Glycoprotein (ABCB11) Knockout Mice

Abstract: In vertebrates, bile flow is essential for movement of water and solutes across liver canalicular membranes. In recent years, the molecular motor of canalicular bile acid secretion has been identified as a member of the ATP binding cassette transporter (ABC) superfamily, known as sister of P-glycoprotein (Spgp) or bile salt export pump (Bsep, ABCB11). In humans, mutations in the BSEP gene are associated with a very low level of bile acid secretion and severe cholestasis. However, as reported previously, becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(106 citation statements)
references
References 32 publications
(63 reference statements)
4
99
2
1
Order By: Relevance
“…Our finding that Pgp knockout mice do not maintain gallbladder bile composition (Figure 6) compliments the recent report by Ling et al who used triple knockout mice to demonstrate that Pgp acts as a compensatory bile salt efflux transporter in the absence of the Bile Salt Export Pump (BSEP) 36,44 . Our gallbladder bile data suggest that Pgp may also be required for bile salt homeostasis under physiologically relevant dietary conditions, even in the presence of BSEP.…”
Section: Discussionsupporting
confidence: 90%
“…Our finding that Pgp knockout mice do not maintain gallbladder bile composition (Figure 6) compliments the recent report by Ling et al who used triple knockout mice to demonstrate that Pgp acts as a compensatory bile salt efflux transporter in the absence of the Bile Salt Export Pump (BSEP) 36,44 . Our gallbladder bile data suggest that Pgp may also be required for bile salt homeostasis under physiologically relevant dietary conditions, even in the presence of BSEP.…”
Section: Discussionsupporting
confidence: 90%
“…This observation may indicate that mouse Mdr1a could act as a salvage transporter for bile salts in conditions of high intracellular bile salt concentration. Transport studies using canalicular plasma membrane vesicles from Bsep knockout animals revealed a residual ATP-dependent transport activity for taurocholate [52]. Plasma membrane vesicles isolated from a drug-resistant Chinese hamster ovary cell line expressing high levels (about 15% of total plasma membrane proteins) of class I P-glycoprotein also exhibit ATP-dependent bile salt transport, albeit with lower affinity than Bsep [52].…”
Section: Mice With Genetically Altered Bsep Expressionmentioning
confidence: 99%
“…Transport studies using canalicular plasma membrane vesicles from Bsep knockout animals revealed a residual ATP-dependent transport activity for taurocholate [52]. Plasma membrane vesicles isolated from a drug-resistant Chinese hamster ovary cell line expressing high levels (about 15% of total plasma membrane proteins) of class I P-glycoprotein also exhibit ATP-dependent bile salt transport, albeit with lower affinity than Bsep [52]. Hence, Mdr1 may act as a salvage system for bile salts in case of nonfunctional or impaired Bsep.…”
Section: Mice With Genetically Altered Bsep Expressionmentioning
confidence: 99%
“…Furthermore, mice with an ablated Bsep gene do not develop severe cholestasis on a normal diet (77), but need to be put on a high cholate diet (78). As a consequence of absent Bsep, novel, more hydrophilic bile salts have been detected in the bile of knockout animals (77) as well as an upregulation of p-glyocoprotein, which could provide a salvage pathway for bile salts (79). Nevertheless, Bsep knockout mice can be used to develop novel therapeutic approaches, such transplantation of cells to correct consequences of non-functional BSEP (80).…”
Section: Discussionmentioning
confidence: 99%